2016
DOI: 10.1017/s0007114516000842
|View full text |Cite
|
Sign up to set email alerts
|

Supplementation of branched-chain amino acids to a reduced-protein diet improves growth performance in piglets: involvement of increased feed intake and direct muscle growth-promoting effect

Abstract: The aim of this study was to investigate whether supplementing branched-chain amino acids (AA) (BCAA) along with a reduced-protein diet increases piglet growth, and whether elevated feed intake and muscle growth-promoting effect contribute to this improvement. In Expt 1, twenty-eight weanling piglets were randomly fed one of the following four diets: a positive control (PC) diet, a reduced-protein negative control (NC) diet, an NC diet supplemented with BCAA to the same levels as in the PC diet (test 1 (T1)) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
41
0
6

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(53 citation statements)
references
References 40 publications
6
41
0
6
Order By: Relevance
“…The response appeared mediated by enhanced activation of the mTOR signalling pathway, as indicated by enhanced phosphorylation of 4E-BP1 and S6K1, resulting in increased efficiency of mRNA translation and competitively using EAAs for protein synthesis (Anthony et al, 2004;Averous, Gabillard, Seiliez, & Dardevet, 2012;Averous et al, 2016;Guo et al, 2018). Hong and Layman (1984) found that leucine supplementation increased skeletal muscle weight, and others also found that BCAAs increased the LD muscle weight in piglets (Zheng et al, 2016(Zheng et al, , 2017 and promoted skeletal muscle protein synthesis (Zheng et al, 2017). The present study also found that leucine supplementation promoted the development of LD muscle.…”
Section: Discussionmentioning
confidence: 99%
“…The response appeared mediated by enhanced activation of the mTOR signalling pathway, as indicated by enhanced phosphorylation of 4E-BP1 and S6K1, resulting in increased efficiency of mRNA translation and competitively using EAAs for protein synthesis (Anthony et al, 2004;Averous, Gabillard, Seiliez, & Dardevet, 2012;Averous et al, 2016;Guo et al, 2018). Hong and Layman (1984) found that leucine supplementation increased skeletal muscle weight, and others also found that BCAAs increased the LD muscle weight in piglets (Zheng et al, 2016(Zheng et al, , 2017 and promoted skeletal muscle protein synthesis (Zheng et al, 2017). The present study also found that leucine supplementation promoted the development of LD muscle.…”
Section: Discussionmentioning
confidence: 99%
“…Так, многочислен-ные модельные эксперименты свидетельст-вуют о значительном анаболическом эффек-те по отношению к мышцам дополнитель-ного приема как отдельных аминокислот, так и их смесей [3][4][5]. При этом отмечено, что наибольшим эффектом в направлении стимуляции мышечного анаболизма облада-ют аминокислоты с разветвленным углево-дородным радикалом [6,7]. Среди амино-кислот этой группы максимальная анаболи-ческая активность обнаруживается у лейци-на [8].…”
unclassified
“…Примечание: цифрами над столбцами указаны номера групп, с которыми имелись статистически значимые (р<0,05) различия лирующее действие на метаболизм угле-водов в печени, предупреждая повышен-ное их накопление, которое отмечалось на избыточной углеводной диете у животных 2-й группы. Наблюдаемый широкий спектр воздействия исследуемых амино-кислот на обмен основных веществ в мышцах и печени связан, по-видимому, с тем, что в организме млекопитающих в условиях недостаточности белка данные аминокислоты могут играть роль систем-ного регулятора (кофактора) как на фер-ментном, так и генетическом уровне, что согласуется с результатами ряда предше-ствующих работ [6][7][8][9].…”
unclassified
“…Так, многочисленные модельные эксперименты свидетельствуют о значительном анаболическом эффекте по отношению к мышцам дополнительного приема как отдельных аминокислот, так и их смесей [3][4][5]. При этом отмечено, что наибольшим эффектом в направлении стимуляции мышечного анаболизма обладают аминокислоты с разветвленным углеводородным радикалом [6,7]. Среди аминокислот этой группы максимальная анаболическая активность обнаруживается у лейцина [8].…”
unclassified
“…На этом фоне у мышей данной группы отмечалась тенденция к снижению уровня общего белка в мышцах.. лирующее действие на метаболизм углеводов в печени, предупреждая повышенное их накопление, которое отмечалось на избыточной углеводной диете у животных 2-й группы. Наблюдаемый широкий спектр воздействия исследуемых аминокислот на обмен основных веществ в мышцах и печени связан, по-видимому, с тем, что в организме млекопитающих в условиях недостаточности белка данные аминокислоты могут играть роль системного регулятора (кофактора) как на ферментном, так и генетическом уровне, что согласуется с результатами ряда предшествующих работ [6][7][8][9].…”
unclassified